Pass-through of cocoa prices along the supply chain: What's left for farmers in Côte D'Ivoire? - Gunther Bensch; Kathrin Kaestner; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Cocoa farmers in Côte d'Ivoire face precarious livelihoods. Low farm-gate prices that are a fraction of the world market price compel land-extensive farming practices that perpetuate a cycle of poverty and environmental degradation. This paper seeks to understand the drivers of the low pass-through of cocoa prices in the world's largest cocoa-producing country and to identify potential inefficiencies and remedies. The analysis comprehensively covers price formation along all segments of the in-country supply chain. Our approach couples econometric analyses using secondary cocoa price data and primary farm household survey data with qualitative assessments of institutional factors specific to the cocoa value chain in Côte d'Ivoire. Notwithstanding the country's highly regulated system of setting cocoa prices, we do not find evidence for inefficiencies that would explain persistently low farm-gate prices. Nor do we find that the recently introduced ''Living Income Differential'', a price premium on internationally traded cocoa, has benefited farmers. We conclude by advocating for the international cocoa industry to strengthen its development programmes in cocoa-growing communities, complemented by government provision of infrastructure and other public goods. Such efforts can ultimately serve to increase the opportunity cost of cocoa production, drawing farmers into other employment sectors while improving the resilience and livelihoods of those who remain. – – Die Kakaobauern in Côte d'Ivoire leben in prekären Verhältnissen. Niedrige Ab-Hof-Preise, die nur einen Bruchteil des Weltmarktpreises ausmachen, zwingen sie zu einer flächenextensiven Bewirtschaftung, die einen Kreislauf aus Armut und Umweltzerstörung aufrechterhält. In diesem Papier wird versucht, die Ursachen für die geringe Weitergabe der Kakaopreise im größten Kakaoanbauland der Welt zu verstehen und mögliche Ineffizienzen und Abhilfemaßnahmen zu ermitteln. Die Analyse umfasst die Preisbildung in allen Segmenten der Lieferkette des Landes. Unser Ansatz verbindet ökonometrische Analysen unter Verwendung sekundärer Kakaopreisdaten und primärer Erhebungsdaten der landwirtschaftlichen Haushalte mit qualitativen Bewertungen institutioneller Faktoren, die für die Kakao-Wertschöpfungskette in Côte d'Ivoire spezifisch sind. Trotz des stark regulierten Systems zur Festsetzung der Kakaopreise in Côte d'Ivoire finden wir keine Hinweise auf Ineffizienzen, die die anhaltend niedrigen Ab-Hof-Preise erklären würden. Wir finden auch nicht, dass das kürzlich eingeführte "Living Income Differential", ein Preisaufschlag auf international gehandelten Kakao, den Bauern zugute gekommen ist. Abschließend plädieren wir dafür, dass die internationale Kakaoindustrie ihre Entwicklungsprogramme in den Kakaoanbaugemeinden verstärkt und durch die Bereitstellung von Infrastruktur und anderen öffentlichen Gütern durch die Regierung ergänzt. Solche Bemühungen können letztlich dazu dienen, die Opportunitätskosten der Kakaoproduktion zu erhöhen und die Bauern in andere Beschäftigungsbereiche zu locken, während sie gleichzeitig die Widerstandsfähigkeit und den Lebensunterhalt derjenigen verbessern, die bleiben.
Keywords: O12; O13; Q11; 330; Cocoa; pass-through; price; policy impact; value chain